PRIVACY RIGHTS IN THE RESPONSIBILITY PERSONAL DATA PROTECTION - Hidayah, Ardiana (Faculty of Law, Universitas Pekalongan, 2024)
Protection of personal data privacy for e-commerce service users has a major influence on a country, including Indonesia, in the development of the digital economy. This protection is an important factor for trust in online transactions and is especially important in digital transactions. Policies regarding personal data and information in the event of a data leak still do not specifically regulate liability provisions in e-commerce . This research discusses the study of legislation regarding the principle of dignified responsibility in carrying out e-commerce transactions in the context of personal data protection in Indonesia. This research is normative legal research based on library research . This research is based legal responsibility in Law Number 27 of 2022 concerning Protection of Personal Data in a proportional balance in protecting users' personal data.